2020
DOI: 10.1109/access.2020.2991861
|View full text |Cite
|
Sign up to set email alerts
|

Availability-Reliability-Stability Trade-Offs in Ultra-Reliable Energy-Harvesting Cognitive Radio IoT Networks

Abstract: With the rise of the Internet-of-Things (IoT), new requirements have been brought into communication networks to make them more efficient, sustainable, and self-sufficient. Requirements, such as availability and ultra-reliability combined with the solutions of energy-harvesting and dynamic spectrum access, make the analyses of such networks more complex, while imposing different performance trade-offs. This paper analyzes the performance of ultra-reliable energy-harvesting cognitive radio Internet-of-Things (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Availability and ultrareliability demands, together with energy-harvesting technology and dynamic spectrum access, impose specific performance compromises [ 79 ], typifying sustainable and self-sufficient IoT networks, integrating sensing time, energy availability, transmission diversity, volume of data frame packets, and spectrum accessibility. Energy and spectrum resource scarcity, energy harvesting and cognitive radio technologies, and wireless devices and system expansion [ 80 ] shape deep-learning-based IoT network performance.…”
Section: Energy-harvesting Technology For Cognitive-radio-based Iot N...mentioning
confidence: 99%
“…Availability and ultrareliability demands, together with energy-harvesting technology and dynamic spectrum access, impose specific performance compromises [ 79 ], typifying sustainable and self-sufficient IoT networks, integrating sensing time, energy availability, transmission diversity, volume of data frame packets, and spectrum accessibility. Energy and spectrum resource scarcity, energy harvesting and cognitive radio technologies, and wireless devices and system expansion [ 80 ] shape deep-learning-based IoT network performance.…”
Section: Energy-harvesting Technology For Cognitive-radio-based Iot N...mentioning
confidence: 99%
“…In addition, a trained artificial neural network (ANN) was used to make decisions regarding PU channel occupancy [2]. Alternatively, [3] used a cluster-based cooperative spectrum sensing method to find the channel's status [16][17][18][19][20]. Recent work by the authors of [4] has proposed an iterative algorithm for interweave CR-IoT devices that incorporate a dynamic sensing threshold and sensing time.…”
Section: Hybrid Spectrum Access (Has)mentioning
confidence: 99%
“…[17]'s researchers discovered that in low SNR environments, the energy detector with a dynamic sensing threshold provides better results than one with a fixed threshold. Another study by [18][19][20][21][22][23][24] used an adaptive sensing threshold for CR-IoT devices using interweave spectrum access. Their results showed that the dynamic sensing threshold improves the ability of the energy detector to combat noise uncertainties and, therefore, spends less time sensing.…”
Section: Related Work and Main Contributionsmentioning
confidence: 99%